An interuser interference suppression approach in full‐duplex wireless communications. Issue 3 (17th January 2018) - Wu, Fei; Pu, Xumin; Zhang, Mintao; Li, Si; Ma, Wanzhi
Abstract: Considering that a full‐duplex network is composed of a full‐duplex base station (BS) and 2 half‐duplex users, one user transmits on the uplink channel and the other receives through the downlink channel on the same frequency. The uplink user will generate interuser interference (IUI) on the downlink user through the interference channel. In this paper, we propose a novel IUI suppression scheme when the BS knows the full channel state information. The main idea of this scheme is to retransmit the weighted uplink signal as soon as it has been received by the BS. For the narrowband case, we first assess the performance of the proposed scheme through simulation with residual self‐interference at the BS. Specially, we derive the closed‐form expression of the optimum weighted coefficient when self‐interference is perfectly canceled at the BS and then discuss the performance of the proposed IUI suppression scheme in practical considerations. Furthermore, the proposed IUI suppression scheme can be extended to the broadband case using a time‐domain weighted filter. Simulation results show the advantage over existing IUI suppression schemes. Abstract : We propose a BS assisting in the IUI suppression scheme and analyze the performance under residual SI. The performance of the proposed IUI suppression scheme is furthermore evaluated under practical considerations such as imperfect channel information, delay difference between IUI and the IUI suppression signals, power control, and limited total transmit power. Besides the newest IUI suppression scheme, we compared the performance of the proposed IUI suppression scheme with the HD mode, the ideal FD mode without IUI, and the FD mode with IUI but not suppressed.